Contribuições do Programa Híbrido de Mentoria (PHM) da UFSCar para o desenvolvimento profissional docente: perspectiva de professoras iniciantes - Barros, Janailza Moura de Sousa (2021)
This dissertation aimed to identify and analyze if / and how the Hybrid Mentoring Program (HMP) contributed to the professional development of beginning teachers participating in it. The data analyzed was from oral and written narratives. HMP is a program that monitors and assists early-career teachers. The theoretical framework was based on the literature on teacher education, teaching profession, beginning teacher, learning about teaching, professional development of teaching and induction programs. The data used in this investigation refer to the narratives and productions developed in the Virtual Learning Environment (VLE) by four beginning teachers of the Early Years of Elementary Education and, also, an interview (online) contemplating aspects related to the education process, pedagogical practices and the learning developed during the program. The data showed that the main motivations of teachers to join the program were related to the possibility of: sharing knowledge; learning from more experienced teachers; improving teaching practice. Regarding the expectations listed by the teachers, they were directed to: sharing experiences, difficulties, insecurities; learning new knowledge; answering questions regarding the classroom, the student; improving teaching action and assisting students in difficulties. Meanwhile, the manifested / perceived demands related to several scenarios: i. Class management: working with students, learning difficulties, with different classes regarding the level of learning; student behavior; unforeseen events; students' difficulties in the subjects of Portuguese and mathematics; difficulty in recognizing and working with students Target Audience of Special Education. ii. Teaching-Learning Process: how to design and apply activities according to the students' specificities; plan, develop and execute classes; how to work with students' difficulties in Portuguese and mathematics; iii. Teaching profession: insecurity and lack of experience; iv. School: handling and using materials requested / made available by the institution and / or educational agency. Regarding the knowledge base for teaching, the data showed little presence of pedagogical knowledge of the content; the existence of some evidence of the specific content domain; and what was most highlighted: general pedagogical knowledge domain. Finally, the contributions of participation in the program mentioned by the teachers were: i. For / by students: advances in reading, writing, interpreting and rewriting texts; progress in performing mathematical activities; improvement in student behavior, in group work. ii. For teaching practice: development of new teaching strategies; interact with students, with content; improvement in teaching practice; dealing with student behavior; greater security in planning, in the development of diversified / specific activities for each student; learned about evaluation strategies; understood how to perceive the students' level of difficulty / learning, how to assist in group work; organize the routine; improvement in the relationship with the children's families; iii. For the professional development of teachers: improving the knowledge base for teaching and the pedagogical reasoning process; they learned about the profession, training/education, identity and teaching responsibility; what it means to be a teacher (good teacher); about the classroom, students; about teaching practice.